Innovation in postgraduates teaching: andragogy theory consideration for MBA executive class / Samsudin Wahab, Basharudin Abdul Hadi and Nor Aminin Khalid - Wahab, Samsudin; Abdul Hadi, Basharudin; Khalid, Nor Aminin (UiTM Press, 2020)
The personal development and direction of postgraduate's education is becoming increasingly important, composite, and confusing. The higher education has an effect on the society through policy- making, funding, and planning. Center for postgraduate studies have to manage and implementing adult learning theories intensively and innovatively in university operation in order to attract more postgraduate admission. The purpose of this paper is to clarify the important element of student participation, comunity involvement in upgrading postgraduate student and motivation. Findings show that by complying with the andragogy theory and community involvement can grab more collaboration partners and increase the number of admission especially for postgraduate program in branch campus. Final recommendation and conclusion are presented at the end of paper.